Requirements engineering : foundation for software quality : 25th International Working Conference, REFSQ 2019, Essen, Germany, March 18-21, 2019, Proceedings /: foundation for software quality : 25th International Working Conference, REFSQ 2019, Essen, Germany, March 18-21, 2019, Proceedings. (2019) - Unknown
No abstract available